Reactive oxygen species and chemokines: Are they elevated in the esophageal mucosa of children with gastroesophageal reflux disease? - ÇELİKEL, ÇİĞDEM; ERTEM ŞAHİNOĞLU, DENİZ; TUTAR, ENGİN; HAKLAR, GONCAGÜL (W J G PRESS, 2008)
AIM: To determine the role of inflammatory cytokines and reactive oxygen species (ROS) in childhood reflux esophagitis. METHODS: A total of 59 subjects who had complaints suggesting GERD underwent esophagogastroduoden oscopy. Endoscopic and histopathologic diagnosis of reflux esophagitis was established by Savary-Miller and Vandenplas grading systems, respectively. Esophageal biopsy specimens were taken from the esophagus 20% proximal above the esophagogastric junction for conventional histopathological examination and the measurements of ROS and cytokine levels. ROS were measured by chemiluminescence, whereas IL-8 and MCP-1 levels were determined with quantitative immunometric ELISA on esophageal tissue. Esophageal tissue ROS, IL-8 and MCP-1 levels were compared among groups with and without endoscopic/histopathologic esophagitis. RESULTS: Of 59 patients 28 (47.5%) had normal esophagus whereas 31 (52.5%) had endoscopic esophagitis. In histopathological evaluation, almost 73% of the cases had mild and 6.8% had moderate degree of esophagitis. When ROS and chemokine levels were compared among groups with and without endoscopic esophagitis, statistical difference could not be found between patients with and without esophagitis. Although the levels of ROS, IL-8 and MCP-1 were found to be higher in the group with histopathological reflux esophagitis, this difference was not statistically significant. CONCLUSION: These results suggest that the grade of esophagitis is usually mild or moderate during childhood and factors apart from ROS, IL-8 and MCP-1 may be involved in the pathogenesis of reflux esophagitis in children. (C) 2008 The WJG Press. All rights reserved.
Keywords: gastroesophageal reflux disease; reflux esophagitis; reactive oxygen species; interleukine-8; monocyte chemoattractant protein-1; INFLAMMATORY BOWEL-DISEASE; MONOCYTE-CHEMOATTRACTANT PROTEIN-1; PYLORI-ASSOCIATED GASTRITIS; FACTOR-KAPPA-B; FREE-RADICALS; ENHANCED EXPRESSION; SUPEROXIDE ANION; NITRIC-OXIDE; INFANTS; PEPSIN